Effects of change in slab geometry on the mantle flow and slab fabric in Southern Peru. Issue 10 (9th October 2016) - Knezevic Antonijevic, Sanja; Wagner, Lara S.; Beck, Susan L.; Long, Maureen D.; Zandt, George; Tavera, Hernando
Abstract: The effects of complex slab geometries on the surrounding mantle flow field are still poorly understood. Here we combine shear wave velocity structure with Rayleigh wave phase anisotropy to examine these effects in southern Peru, where the slab changes its geometry from steep to flat. To the south, where the slab subducts steeply, we find trench‐parallel anisotropy beneath the active volcanic arc that we attribute to the mantle wedge and/or upper portions of the subducting plate. Farther north, beneath the easternmost corner of the flat slab, we observe a pronounced low‐velocity anomaly. This anomaly is caused either by the presence of volatiles and/or flux melting that could result from southward directed, volatile‐rich subslab mantle flow or by increased temperature and/or decompression melting due to small‐scale vertical flow. We also find evidence for mantle flow through the tear north of the subducting Nazca Ridge. Finally, we observe anisotropy patterns associated with the fast velocity anomalies that reveal along strike variations in the slab's internal deformation. The change in slab geometry from steep to flat contorts the subducting plate south of the Nazca Ridge causing an alteration of the slab petrofabric. In contrast, the torn slab to the north still preserves the primary (fossilized) petrofabric first established shortly after plate formation. Key Points: Slab tear in southern Peru north of the Nazca Ridge created new mantle pathway Pronounced low‐velocity anomaly is detected beneath the flat slab Slab anisotropy reflects substantial along strike variations in the slab's internal deformation